Is Acteoside Effects on Colon Cancer Stem Cells Via Inflamation or Apoptosis? - Hafize Seda Vatansever; Feyzan Ozdal Kurt; Canan Türkoğlu; Fatma Fırat (Genel Tıp Dergisi, 2022)
AIM: Colon cancer is one of the main health problems worldwide. Cancer stem cells (CSCs) are referred to as tumor-initiating cells involved in tumor heterogeneity and dormancy. CSCs can cause drug resistance, metastasis, and recurrence of primary and metastatic cancers. The interactions and survival trends of colon cancer stem cells with other cells may be an alternative route for effective treatment. In our study, we aimed to evaluate the effects of asteoside on stem cell properties, apoptotic and inflammatory processes in primary (HCT-116) and metastatic (Colo-741) colon CSCs. METHERIALS AND METHODS: CSCs were obtained from both types of colon cancer cell lines with the MINIMACS system using the anti-CD133 reagent. Metastatic Colo-741 and non-metastatic HCT-116 CD133+ and CD133- cells were cultured with or without Acteoside for 48 hours. Expressions of Caspase-3, Bcl, Bax, and Fas-L for apoptosis, and IL-1β, TNF-α, IL-6, IL8 and IL-10 for inflammation were analyzed by indirect immunocytochemistry technique by performing H-Score. Changes in cell morphology were examined under an inverted microscope. RESULTS AND CONCLUSION: It was observed that Oct-4 expression decreased after acteocyte administration in both metastatic and non-metastatic colon cancer cells. In addition, Colo-741 increased the intensity of the Bax/Bcl ratio in both CD133+ and CD133- cells and increased caspase 3 expression. While acteoside did not immunohistochemically affect inflammation in metastatic COLO-741 cells, it contributed to the apoptotic process by changing the Bax/Bcl ratio. When the morphology of the cells was evaluated, it was observed that the number of apoptotic cells increased in COLO-741 CD133+ and CD133- cells.